ANALISIS SWOT PEMASARAN DIGITAL CV RAMINDO KARYA MENGGUNAKAN TIKTOK ADS DAN FACEBOOK ADS DALAM ERA DIGITAL - Yuwanasari, Ghishela; Izazi, Zsa Zsa (PUTRA JAWA PUBLISHER, 2024)
This paper discusses the analysis of the digital marketing strategy of the CV Ramindo Karya Company using two main platforms, namely TikTok Ads and Facebook Ads. This research uses a qualitative research method with a case study approach. The aim is to ensure the effectiveness of CV Ramindo Karya's digital advertising campaign in supporting the company's marketing objectives. SWOT analysis is used to reveal strengths, weaknesses, opportunities and threats. Based on the results of the analysis, various strategies can be formulated to take advantage of strengths and opportunities, as well as weaknesses and threats to overcome. The implementation of the strategy is expected to increase the competitiveness of CV Ramindo Karya in the future.